2017
DOI: 10.1152/ajpregu.00263.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate supplementation and exercise tolerance in patients with heart failure with reduced ejection fraction

Abstract: Endothelial dysfunction and reduced nitric oxide (NO) signaling are key abnormalities leading to skeletal muscle oxygen delivery-utilization mismatch and poor physical capacity in patients with heart failure with reduced ejection fraction (HFrEF). Oral inorganic nitrate supplementation provides an exogenous source of NO that may enhance locomotor muscle function and oxygenation with consequent improvement in exercise tolerance in HFrEF. Thirteen patients (left ventricular ejection fraction ≤40%) were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 63 publications
4
40
3
Order By: Relevance
“…We observed DStO 2 values ranging from À1% to À7%. This magnitude of change aligns with previous cycling exercise studies (Okushima et al 2015;Hirai et al 2017).…”
Section: Skeletal Muscle Oxygenation and Rpesupporting
confidence: 90%
“…We observed DStO 2 values ranging from À1% to À7%. This magnitude of change aligns with previous cycling exercise studies (Okushima et al 2015;Hirai et al 2017).…”
Section: Skeletal Muscle Oxygenation and Rpesupporting
confidence: 90%
“…Nutrition interventions to improve CRF in HFrEF patients have included micronutrient supplementation [76], amino acids (AA) [77][78][79][80][81], nutrition support supplementation [84], N-3 PUFA [82,83], and dietary nitrates [85,86].…”
Section: Heart Failurementioning
confidence: 99%
“…The authors suggested that this may have been related to inadequate dosing; however, a recent trial of inhaled nitrates without ET also failed to increase peak VO 2 in subjects with HFpEF [93]. Dietary nitrate supplementation has also resulted in mixed effects on CRF in small pilot trials of subjects with HFrEF without ET [85,86]. Currently, the INABLE-Training trial (NCT02713126) is combining higher dosing of oral nitrates with a cardiac rehabilitation (CR) program for 12 weeks in a double-blind, randomized placebo-controlled trial of patients with HFpEF on a primary outcome of peak VO 2 .…”
Section: Dietary Nitrate Supplementation In Hfpefmentioning
confidence: 99%
“…Dietary nitrate supplementation elicits a number of physiological effects, such as increased skeletal muscle blood flow during exercise , decreased blood pressure and improved exercise performance and tolerance (Webb et al ., ,; Kapil et al ., ; Kenjale et al ., ; Lansley et al ., ; Lundberg et al ., ; Cermak et al ., ; Ferguson et al ., , ; Bailey et al ., ; Casey et al ., ; Hirai et al ., ). Our laboratory recently demonstrated nitrate supplementation augments cutaneous vasodilatation to both local heating and whole‐body heating (Keen et al ., ; Levitt et al ., ).…”
Section: Introductionmentioning
confidence: 97%